IMPLEMENTATION OF RISK MANAGEMENT PLANNING IN INFRASTRUCTURE PROJECT WITH PUBLIC PRIVATE PARTNERSHIP (PPP) SCHEME â CASE STUDY IN LRT MEDAN PROJECT PT LEN INDUSTRI (PERSERO) - Atma Hadi, Nugroho
Exposure of risk always exist in project management activities in the company, including project management in PT Len Industri (Persero) which one of its business related to railway transportation infrastructure. In consequence, the company should manage project risk with right framework to assure project objectives can be achieved. Previously, the company carry out risk identification and risk assessment only by following worksheet template available which using qualitative approach. It can generates uncomplete and subjective result that can lead to inappropriate risk treatment. The impact from inappropriate risk treatment on previous project was delay in project implementation and emergence of unexpected additional cost that can reduce profit margin. Therefore, this research will carry out risk identification processes using 5 risk categories that has been developed by Palupi and Yuniarto (2016) combine with SWOT analysis, PESTEL analysis, and stakeholder analysis to generate complete risk identification. Moreover, risk analysis is carried out to know inherent risk of the project using Analytical Hierarchy Process (AHP) developed by Saaty (2008) to get objective risk priority based on eigen value of each risk. Then risk evaluation and risk treatment are carried out based on result of risk analysis which generates risk treatment plan, target of risk residual, and resources needed to carry out risk treatment plan. Object of this research is LRT Medan project that use Public-Private Partnership scheme where now the company still in planning stage. The company acts as a Business Entities (BE) and collaborate with other parties such as Ministry of Transportation (MoT) and Medan Major as Government Contracting Agency (GCA). Risk identification processes which using Forum Group Discussion (FGD) with seven respondents in PT Len Industri (Persero) and related journals show that the company has to consider 5 risk categories, namely Financial Risk, Operational Risk, Construction Risk, Force Majeure Risk, and Revenue Risk. Those risks categories are divided into 23 sub-risk and should be fully anticipated by the company. Risk analysis shows that the project has inherent risk that consist of 1 extreme risk, 21 high risk, and 1 medium risk. Based on risk analysis, risk treatment plan is carried out to reduce likelihood score and / or impact score of each risk. By applying risk treatment plan, project team can expect that risk level of residual risk in the project will be lower than initial risk level of inherent risk.